The Evolutionary History of The Orexin/Allatotropin GPCR Family: From Placozoa and Cnidaria to Vertebrata - Alzugaray, Maria Eugenia (2019)
Peptidic messengers constitute a highly diversified group of intercellular messengers widely distributedin nature that regulate a great number of physiological processes in Metazoa. Being crucial for life, itseem that they have appeared in the ancestral group from which Metazoa evolved, and were highlyconserved along the evolutionary process. Peptides act mainly through G-protein coupled receptors(GPCRs), a family of transmembrane molecules. GPCRs are also widely distributed in nature beingpresent in metazoan, but also in Choanoflagellata and Fungi. Among GPCRs, the Allatotropin/Orexin(AT/Ox) family is particularly characterized by the presence of the DRW motif in the second intracellularloop (IC Loop 2), and seems to be present in Cnidaria, Placozoa and in Bilateria, suggesting that it waspresent in the common ancestor of Metazoa. Looking for the evolutionary history of this GPCRs wesearched for corresponding sequences in public databases. Our results suggest that AT/Ox receptorswere highly conserved along evolutionary process, and that they are characterized by the presenceof the E/DRWYAI motif at the IC Loop 2. Phylogenetic analyses show that AT/Ox family of receptorsreflects evolutionary relationships that agree with current phylogenetic understanding in Actinopterygiiand Sauropsida, including also the largely discussed position of Testudines